Antioxidant, photoprotective and antimutagenic properties of Phyllanthus spp. from Cuban flora - Ivette M. Menéndez-Perdomo; Maylin Wong-Guerra; Fabiana Fuentes-León; Elizabeth Carrazana; Isis Casadelvalle; Alexis Vidal; Ángel Sánchez-Lamar (GarVal Editorial Ltda., 2017)
Context: Sunlight ultraviolet (UV) radiation constitutes a significant physical carcinogen in nature. It could induce direct and indirect DNA damage, which if not properly repaired may generate mutations. Plants in the genus Phyllanthus (Phyllanthaceae) are widely used in traditional medicine and known as natural sources of antioxidant compounds. Recent investigations support their genoprotective activity against chemical and physical mutagens, among them UV radiation. Aims: To compare the antioxidant, photoprotective and antimutagenic activity of aqueous extracts obtained from three Cuban endemic Phyllanthus species: P. chamaecristoides Urb., P. microdictyus Urb., and P. williamioides Gr. Methods: DPPH radical scavenging assay was use for quantify the in vitro antioxidant capacity. Genoprotection against UVC radiation was measured at two levels: structural DNA damage and mutations, by means of the SOS Chromotest, Survival assay, and RifR mutagenicity test in Caulobacter crescentus cells. Results: P. chamaecristoides extract showed the highest antioxidant capacity (IC50 = 0.032 mg/mL), and together with P. microdictyus exhibited the greatest bioantimutagenic effects (RMF ≤ 5%), diminishing UVC-induced DNA damage in three and five times, respectively. Conclusions: The reduction in DNA damage is not founded in a Phyllanthus aqueous extracts desmutagenic effect. It is possible that the genoprotective activity detected could be due to modulation of DNA repair mechanisms, diminishing SOS response and related mutagenicity induced by UVC radiation. Moreover, high antioxidant capacity could also decrease UV radiation oxidative-damage. Altogether, these outcomes validate future pre-clinic research regarding Phyllanthus photoprotective capacities.